Perkembangan Jiwa Keberagamaan Pada Anak Usia 4- 6 Tahun - Lubis, Ramadan; Harahap, Army Fahita; Lubis, Iga Nailah Aulia Br; Fitriyani, Nuri Al; Brutu, Sabila Meliani; Rais, Syazwina Dinda Damara (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of the religious spirit in children is generally an early development, but actually even before childhood, a child has received an education about religion, namely in the womb, paranatal period and infancy. According to Zakiyah Darajat, children's religious spirit develops in line with their physical and psychological development. The aim of this research is to find out how religious beliefs and values shape their psychological aspects. This research discusses the development of religious spirit in children, the role of parents in instilling religious values in children. This research uses a combined method of observation, interviews, and literature study to gain an in-depth understanding of how children internalize and develop dimensions of their spirituality as they grow. The results of this study provide a better view of the significant role that environmental influences play in shaping children's religious identities, with important implications for future education and moral formation.